Dual action of highbush blueberry proanthocyanidins on Aggregatibacter actinomycetemcomitans and the host inflammatory response - Amel Ben Lagha; Geneviève LeBel; Daniel Grenier (BMC, 2018)
Abstract Background The highbush blueberry (Vaccinium corymbosum) has a beneficial effect on several aspects of human health. The present study investigated the effects of highbush blueberry proanthocyanidins (PACs) on the virulence properties of Aggregatibacter actinomycetemcomitans and macrophage-associated inflammatory responses. Methods PACs were isolated from frozen highbush blueberries using solid-phase chromatography. A microplate dilution assay was performed to determine the effect of highbush blueberry PACs on A. actinomycetemcomitans growth as well as biofilm formation stained with crystal violet. Tight junction integrity of oral keratinocytes was assessed by measuring the transepithelial electrical resistance (TER), while macrophage viability was determined with a colorimetric MTT assay. Pro-inflammatory cytokine and MMP secretion by A. actinomycetemcomitans-stimulated macrophages was quantified by ELISA. The U937-3xκB-LUC monocyte cell line transfected with a luciferase reporter gene was used to monitor NF-κB activation. Results Highbush blueberry PACs reduced the growth of A. actinomycetemcomitans and prevented biofilm formation at sub-inhibitory concentrations. The treatment of pre-formed biofilms with the PACs resulted in a loss of bacterial viability. The antibacterial activity of the PACs appeared to involve damage to the bacterial cell membrane. The PACs protected the oral keratinocytes barrier integrity from damage caused by A. actinomycetemcomitans. The PACs also protected macrophages from the deleterious effect of leukotoxin Ltx-A and dose-dependently inhibited the secretion of pro-inflammatory cytokines (IL-1β, IL-6, CXCL8, TNF-α), matrix metalloproteinases (MMP-3, MMP-9), and sTREM-1 by A. actinomycetemcomitans-treated macrophages. The PACs also inhibited the activation of the NF-κB signaling pathway. Conclusion The antibacterial and anti-inflammatory properties of highbush blueberry PACs as well as their ability to protect the oral keratinocyte barrier and neutralize leukotoxin activity suggest that they may be promising candidates as novel therapeutic agents.